PENGGUNAAN PROPORTIONAL INTEGRAL DERIVATIVE ( PID ) CONTROLLER PADA FILTER AKTIF UNTUK MEREDAM HARMONISA AKIBAT BEBAN NON LINIER DI BALI NATIONAL GOLF RESORT - Widiarsana, I Gusti Made; Rinas, I Wayan; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2018)
Bali National Golf Resort has a high level of non-linear load usage. A harmonic is emerged due to a high level of non-linear load usage which was the main problem on the quality of electric power. On the other hand, it is also lead to an adverse impact for the electric power system such as the wave form and voltage were not sinusoidal. Then, in order to reduce it, an active filter could be used as one of the best way. This research focused on the simulation of PID (Proportional Integral Derivate) Controller towards an active filter to reduce the harmonic and MATLAB R2013 software that applicated as the instrument. As the result,the usage of PID Controller on the active filter could reduce the THDi into 1.89% and THDv into 0.59 % as an average percentage at Bali National Golf Resort.